UPAYA PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM PENGELOLAAN KEUANGAN TAHUN 2011-2012 - Sary, Desia Novita; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Regional Autonomy through Act No. 32 of 2004 on Regional Government does not just move the bulk of the authority of the Central Government to Local Government but Act No. 32 of 2004 should bring meaning to the welfare of the people in the area has not materialized.This study aims to describe and analyze the efforts made by the Government of Regency Kuantan Singingi in maintaining WTP opinion on the financial statements in 2012 and want to know the limiting factors in the financial management area Singingi Kuantan district. This study used a qualitative approach with descriptive type. The process of data collection is done in the Regency Kuantan Singingi particularly in the Financial Section of the Secretariat of Regent Office Kuantan Singingi using interview techniques and documentation. From the results of the study be concluded that the efforts made by the Government of Kuantan District Singingi in Financial Management Year 2011-2012 is sufficient maximum. Efforts made Singingi Kuantan District Government that is the professionalism of the work Singingi Kuantan District Government, Human Resources for Establishing a quality, appreciation and motivation from leaders to subordinates and has made the Financial Management Information System (SIPKD). But behind the efforts that have been made, there are also some factors inhibiting the Local Government financial management is lalainya most Singingi Kuantan District Government Agencies Kuantan Singingi in UYHD submit to the local treasury.Keywords: Efforts, Financial management